2018
DOI: 10.1186/s13063-018-2881-3
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Autism Communication Therapy-Generalised (PACT-G) against treatment as usual for reducing symptom severity in young children with autism spectrum disorder: study protocol for a randomised controlled trial

Abstract: BackgroundPrior evidence shows that behaviours closely related to the intervention delivered for autism are amenable to change, but it is more difficult to generalise treatment effects beyond the intervention context. We test an early autism intervention designed to promote generalisation of therapy-acquired skills into home and school contexts to improve adaptive function and reduce symptoms. A detailed mechanism study will address the process of such generalisation. Objective 1 will be to test if the PACT-G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 38 publications
(29 reference statements)
5
51
0
Order By: Relevance
“…Therapists need to meet pre-specified criteria regarding their therapy related competencies before being allowed to treat the children within the study and will be supervised regularly during the study period. Most high quality studies in early intervention, such as PACT [14,85] and ESDM [11], reported on their training procedures, which are overall comparable with the one implemented in the present study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therapists need to meet pre-specified criteria regarding their therapy related competencies before being allowed to treat the children within the study and will be supervised regularly during the study period. Most high quality studies in early intervention, such as PACT [14,85] and ESDM [11], reported on their training procedures, which are overall comparable with the one implemented in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…The diagnostic team leader has received training on the BOSCC and the DCMA by the developer of the regarding instruments, before. This procedure has also been reported in similar intervention studies [45,85,86].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, a high sense of self-efficacy is positively related to promising results. For example, it is associated with encouraging in-class behavior, classroom practice, use of praise more often than criticism, increased perseverance with "low achievers," spending more time monitoring student performance, and spending more time on class preparation and paperwork, increased willingness to collaborate with other professionals regarding student concerns, increased significant effort, and increased success [87][88][89][90][91].…”
Section: Asd Self-efficacy Among Preschool Teachersmentioning
confidence: 99%
“…Indeed, the answer will lie in cumulative effectiveness research and the use of common outcome measures across trials so that systematic reviews and meta-analyses can be easily conducted in the future [2]. The current trial prepares for this prospect, adopting measures such as the DCMA and BOSCC used in the PACT-G trial [69], and VABS-2 and the MSEL used in the Early Start Denver Model trial [12] and many other studies of autism. While the current trial is not sufficiently scoped to ascertain whether the Point OutWords intervention is effective in improving communication skills in children with autism, it can inform the design of larger RCTs, not only for Point OutWords but also for other early interventions in autism.…”
Section: Discussionmentioning
confidence: 99%